(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
The financial industry is a pivot of the economy and plays an important social role. Goal of this study was to analyze factors associated with the framing level in banking in the province of Pisa. We collected data about age, gender, framing level, workplace and type of bank for bankers in Pisa through trade unionists. We collected data on 2018 workers and we found significant associations between framing level and aged over 40 years (OR = 4.5; 95% CI: 2.9-6.9), workplace in Pisa (OR = 0.30; 95% CI: 0.20-0.44) and male gender (OR = 2.89; 95% CI: 1.98-4.21). The first two factors are explainable with organizational characteristics. In fact for becoming manager you already have to work a number of year and in cities rather than in the surrounding municipalities, consistent with the size of bank. However, the third factor, already known in the literature in other work areas, requires further studies for explaining causes and helping to implement actions to reduce the gender gap.